Da Rasool Allah : 200 Zareeni Wayanavi - Abdul Malik Mujahid (Lahore Darussalam)
Islam is based on two major sources: the Qur'an and the Sunnah, and the latter is available to us in the form of hadiths. The Prophet (S) said,"Whoever comes to know one hadith of mine should spread it." I have come to the realization that many youth from among the Muslims have not memorized even one hadith of the Prophet (S). For this reason I have chosen smaller hadiths so that they can be easily memorized by them and they can spread them to others. I supplicate to Allah to make this book a source of light on the Day of Judgment for us.
Keywords: Hadiths